RANCANG BANGUN APLIKASI ONLINE UNTUK TEST MINAT BAKAT SISWA SMA DENGAN METODE RIASEC - Palaguna, I Nyoman Terang Trimakna; Yuliansyah, Alfian Fahrul; Sudarma, Made; Suyadnya, I Made Arsa (Peneliti.net, 2024)
This study aims to design and develop online applications with the aim of identifying the interests and talents of high school students using the RIASEC (Realistic, Investigative, Artistic, Social, Enterprising, Conventional) method. This application is intended to help students understand their interests and talents as well as provide guidance in choosing the appropriate educational and career path. The RIASEC method has proven to be an effective tool in analyzing individual interests and talents based on six personality types. This method will be integrated into the application to provide relevant questions and tests to assess student interest and talent. The application will be developed with a user-friendly interface to facilitate easy navigation and accurate evaluation for students. This research will focus on high school students as the main research subject. The data required for the operation of the application will be collected through surveys and interviews involving students from various high schools. In addition, a literature review will be carried out to ensure the accuracy and reliability of the RIASEC method in identifying students' interests and talents. The results of this study are expected to demonstrate the effectiveness of online applications in identifying the interests and talents of high school students using the RIASEC method. The application can be a valuable tool for students, parents and teachers in guiding students towards educational and career choices that match their interests and talents.